THE IMPACT OF THE TECHNICAL REVOLUTION ON HUMAN SOCIAL ACTIVITIES (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article discusses discoveries in the field of production, industry and technology of the 17th-20th centuries and their role in human life. Opinions were expressed about the discovery of new types of economic and political relations as a result of the "big bang" in Europe in industry and technology. The dynamic growth of revolutionary changes in such areas as manufacturing machines, automation and computing is studied.